Involvement of doublecortin-expressing cells in the arcuate nucleus in body weight regulation - Werner, Lars; Ritzal, Manuela; Schwaninger, Markus (Endocrinology, 2012)
Hypothalamic functions, including feeding behavior, show a high degree of plasticity throughout life. Doublecortin (DCX) is a marker of plasticity and neuronal
Gesehen am 26.11.2018